Local and global Solution of fractional Nonlinear Integro-Differential Equation - Ghada Shuker Jameel (College of Education for Pure Sciences, 2013)
ABSTRACT In this paper we study the existence, uniqueness and stability solution of fractional nonlinear integro-differential equation, by using the Picard approximation method , and Banach fixed point method. also we extend some results obtain in .